Road to Recovery : Singapore's Journey through the Global Crisis - Das, Sanchita Basu (Book collections on Project MUSE., 2010)
Singapore had been one of the nations severely affected by the 2008-09 global financial and economic crisis. The city state came under pressure through the financial, trade, and confidence channels. To counter these shocks, Singapore policymakers undertook unprecedented monetary and fiscal policy measures. They subsequently charted a revival strategy that would help the country emerge stronger after the crisis. These all-encompassing policies together with the global economic recovery in 2009 ...